PERAN KOMITE SEKOLAH DALAM PENENTUAN DAN PELAKSANAAN KEBIJAKAN SEKOLAH (STUDI KASUS DI SMK BATIK 2 SURAKARTA) - Asri Sukmawati; Tri Murwaningsih; C Dyah S. Indrawati (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2020)
The objectives of this research are for understanding : (1) Therole of School Committee in determining and implementing policiesin SMK Batik 2 Surakarta. (2) The obstacles that occur in the School Committeein SMK Batik 2 Surakarta. (3) The efforts made to resolve the obstacles that occur in in determining and implementing policiesin SMK Batik 2 Surakarta. This research is using a qualitative descriptive with case study research approach. The sources of data used in this research come from informants, research location, documents and archives. The sampling technique used is purposive sampling and snowball sampling. The data collecting techniques used are interviews, observation,and documentation analysis. The data validations used are data triangulation. Data analysis used is an interactive analysis model and flow analysis model.